UNDER SURVEILLANCE: DECODING THE KEYS TO THE SOCIAL CREDIT SYSTEM AS A MASS SURVEILLANCE PROTOCOL IN THE PEOPLE’S REPUBLIC OF CHINA FOLLOWING THE 19TH NATIONAL CONGRESS OF THE COMMUNIST PARTY OF CHINA - Martínez Andreu, Miguel Ángel (2025)
The social credit system (hereinafter, SCS) is presented as a complete security protocol aimed at mass surveillance which, through the integration of big data and other technological means, is capable of monitoring and evaluating the behavior of the population. Proposed as a novel method after the economic crisis of 2008, this strategy aims to strengthen social trust in the centralized political network undera single-party regime, since, mainly due to the ambiguity of this strategy, it reflects a change in the paradigm of global governance and security, taking advantage of the field of cyber tools with the aim of achieving an unprecedented level of social control in the country of China.